2019
DOI: 10.1002/advs.201801688
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy against Metastatic Melanoma Based on Self‐Assembled Metal‐Phenolic Nanocomplexes Comprised of Green Tea Catechin

Abstract: The targeted therapy of metastatic melanoma is an important yet challenging goal that has received only limited attention to date. Herein, green tea polyphenols, (–)‐epigallocatechin‐3‐gallate (EGCG), and lanthanide metal ions (Sm 3+ ) are used as building blocks to engineer self‐assembled Sm III ‐EGCG nanocomplexes with synergistically enhanced tumor inhibitory properties. These nanocomplexes have negligible systemic toxic effects on healthy cells but cause a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 47 publications
1
93
0
Order By: Relevance
“…For the challenging problem of targeted therapy of metastatic melanoma, the assembly of EGCG and metal shows good results. Using green tea polyphenols, EGCG, and lanthanide metal ions (Sm 3+ ) as building blocks, Li et al ( 2019a ) designed self-assembled Sm-III-EGCG nanocomplexes with synergistic antitumor properties. The systemic toxic effects of these nanocomposites on healthy cells are negligible, but the activity of melanoma cells is significantly reduced by effectively regulating their metabolic pathway.…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…For the challenging problem of targeted therapy of metastatic melanoma, the assembly of EGCG and metal shows good results. Using green tea polyphenols, EGCG, and lanthanide metal ions (Sm 3+ ) as building blocks, Li et al ( 2019a ) designed self-assembled Sm-III-EGCG nanocomplexes with synergistic antitumor properties. The systemic toxic effects of these nanocomposites on healthy cells are negligible, but the activity of melanoma cells is significantly reduced by effectively regulating their metabolic pathway.…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
“…The systemic toxic effects of these nanocomposites on healthy cells are negligible, but the activity of melanoma cells is significantly reduced by effectively regulating their metabolic pathway. Green tea–based self-assembled nanocomposites have all the key features of promising clinical candidates and can address the challenges associated with the treatment of advanced metastatic melanoma (Li et al, 2019a ).…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
“…TheH RP-TA capsules showed comparable catalytic activity to free HRP, thus suggesting that the enzymatic activity was not significantly affected after assembly (Figure 5b and Figure S17). [23] Moreover,these capsules showed higher catalytic activity (ca. 25 %) than the HRP-TAc ore-shell particles,w hich is attributed to the likely improved mass transfer in the hollow (capsule) system.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…In a mouse melanoma tumor model, Sm III –EGCG nanocomplexes are directly compared with a clinical anticancer drug, 5-fluorouracil, and shows remarkable therapeutic effects on primary melanoma tumors and inhibition of metastasis of melanoma from invading other organs through targeted therapeutic effects [86]. Moreover, these results suggested that Sm III –EGCG complexes exhibited significantly lower adverse side effects than 5-fluorouracil when the anticancer therapy was performed on melanoma primary tumors.…”
Section: Phytochemicals Conjugated With Nps As Nanomedicinementioning
confidence: 99%